Health service provision and the use of pressure-redistributing devices: mixed methods study of community dwelling individuals with pressure injuries. Issue 3 (4th May 2017) - Jackson, Debra; Durrant, Lisa; Bishop, Emily; Walthall, Helen; Betteridge, Ria; Gardner, Sarah; Coulton, Wendy; Hutchinson, Marie; Neville, Stephen; Davidson, Patricia M.; Usher, Kim
Abstract : Background : Health care within the home setting is a vital and growing component of pressure injury (PI) prevention and management. Objectives : To describe the use of health services and pressure-redistributing devices in community dwelling patients with PI's. Design : Mixed-methods collective case study of a defined, diverse geographic postcode area in the United Kingdom. Methods : Quantitative retrospective analysis of electronic and paper medical records of adult PI patients from 2015 district nursing reports. Qualitative semi-structured interviews of community dwelling adult patients receiving, or received, treatment for PI in 2016. Results : Mandatory reports ( n = 103) revealed that 90 patients were supplied with a variety of pressure-redistributing devices but only one-third of patients used the equipment as recommended. Qualitative interviews ( n = 12), reported to COREQ guidelines, revealed that patients felt reliant on community health services, and were concerned about the consistency of their care. Conclusions : Authentic patient involvement is required to provide care and interventions that are acceptable to PI patients and can be incorporated into self-care strategies and effectively monitored.